CLONING, EXPRESSION AND STLJDY OF IMMIJNOLOGICAL PROPERTIES OF THE STREPTOCOCCI GROUP B C5A PEPTIDASE RECOMBINANT PROTEIN - N. V. Duplik; I. V. Koroleva; A. N. Suvorov (Медицинская иммунология, 2014)
Molecular mass of SCPB1 was estimated to be equal to 43.0±0.5 kDa. Immunization experiments were performed in laboratory animals to investigate the SCPB1 immunogenic properties. Maximum titers of IgG antibodies against SCPB1 (1:5,1 х 104 и 1:1,6× x 106 for mice and rabbits, respectively) indicated to SCPB1 immunogenicity. Moreover, the antibodies against SCPB1 were revealed in sera from women infected with GBS thus designating the humoral immune response of human organism to C5a peptidase fragment under study. Protective properties of anti-SCPB1 antibodies against were demonstrated by experiments in vitro (opsonophagocytosis), and in vivo (a model of GBS infection in mice).